Mind the Gap Between Theory and Practice: Nursing Students and Tutors in Comparison - Maicol Carvello; Roberto Lupo; Giulia Rum; Elsa Vitale; Luana Conte; Valeria Cremonini; Ivan Rubbi (Iran University of Medical Sciences, 2024)
Background: Internship represents the context for nursing students to acquire professional skills. The mutual relationship between the intern and the tutor, where both parties have the opportunity to grow and develop, contributes to transforming theoretical knowledge into intellectual, psychomotor, and social skills. However, the gap between education and clinical practice has always challenged education experts. This study assesses the gap between the theory learned during lectures and the applied care practice during the internship, highlighting factors opposing knowledge translation. Methods: A prospective observational study was conducted in June and July 2022, involving clinical tutors (48 tutors) and third-year nursing students (107 students) recruited by convenience sampling. Both groups were administered a designed questionnaire built by the researchers, using semi-structured interviews in the related literature and adapted to the Italian context. Two Italian universities participated in the study (University of Bari and Polytechnic University of the Marche, located in Ancona, Italy). Descriptive and Inferential statistics were employed. All P<0.05 were considered statistically significant. The data were analyzed using Jamovi software, version 2.3.18 and Microsoft Office Excel software.  Results: A significant disparity was found between the learned theory and practical care in a hospital setting, with 86.9% of students compared to 60.4% of tutors acknowledging this gap (P<0.0001). In contrast to 60.4% of tutors, 87.9% of students (P<0.0001) declared that theoretical elements were sometimes incomprehensible when applied to practice. Consequently, 78.5% of learners, as opposed to 25.0% of tutors, had to adapt their care behaviors to the methods used in the wards where they were on services (P<0.0001). Conclusions: The study explored some possible reasons underlying the dichotomy between theory and practice, both from the perspective of students and tutors. Both groups perceived the presence of a theory-practice gap but with different implications. While tutors are willing to explain, students express difficulties in expressing doubts regarding the gap. Addressing the theory-practice gap, particularly during the mentoring period, could be a possible solution to bridge the gap. Discussions during the mentoring period would be helpful. These discussion moments are pedagogical, as they could stimulate reflection in students and develop critical thinking.